The Sao Vicente earthquake of 2008 April and seismicity in the continental shelf off SE Brazil: further evidence for flexural stresses - Assumpcao, M.; Dourado, J. C. [UNESP]; Ribotta, L. C.; Mohriak, W. U.; Dias, Fabio L.; Barbosa, J. R. (Wiley-Blackwell, 2011)
The continental margin and shelf of most stable intraplate regions tend to be relatively more seismically active than the continental interior. In the southeast continental margin of Brazil, a seismic zone extends from Rio Grande do Sul to Espirito Santo, with seismic activity occurring mainly along the continental slope and suggesting a close relationship with flexural stresses caused by the weight of the sediments. In this region, earthquakes with magnitudes larger than 5 m(b) occur every 20-25 yr, on average. The focal mechanism solutions of previous earthquakes in this zone indicated reverse faulting on planes dipping approximately 45 degrees. with horizontal P-axes. The recent 5.2 m(b) earthquake of 2008 April 23 occurred 125 km south of Sao Vicente and was well recorded by many stations in SE Brazil, as well as at teleseismic distances in North America and Africa. Its focal depth was 17 km, locating the hypocentre in the lower crust. A well-determined focal mechanism solution shows one vertical nodal plane and one subhorizontal nodal plane. The P- and T-axes exhibit large dips, which were confirmed by a regional moment tensor inversion. This unusual orientation of the fault mechanism can be attributed to a rotation of the principal stress directions in the lower crust caused by flexural effects due to the load of recent sedimentation.
Keywords: Earthquake source observations; Seismicity and tectonics; Intra-plate processes; Lithospheric flexure; South America